RELATIONSHIP BETWEEN CHRONOTYPE AND SLEEP QUALITY AMONG ADOLESCENTS AT JAMBI HIGH SCHOOL - Rama Yani Berutu; Fadliyana Ekawaty; Lisa Anita Sari; Luri Mekeama; Indah Mawarti (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Sleep is a fundamental physiological need that supports adolescents’ cognitive, emotional, and physical development. However, poor sleep quality remains common among adolescents and may be influenced by biological factors such as chronotype. This study aimed to analyze the relationship between chronotype and sleep quality among adolescents at SMA Negeri 8 Jambi City. A quantitative cross-sectional design was used with 103 students selected through stratified random sampling. Chronotype was measured using the Morningness–Eveningness Questionnaire (MEQ), while sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed using univariate and Chi-square tests. The results showed that most respondents had an intermediate chronotype (54.4%) and poor sleep quality (61.2%). Statistical analysis indicated a significant relationship between chronotype and sleep quality (p = 0.020; Cramer’s V = 0.276). Adolescents with evening chronotype tended to experience poorer sleep quality compared with those with morning chronotype.